Mesh-free thin spraying support material and preparation method thereof
Through the component design and preparation method of the gridless thin spray support material, the problems of low bond strength and high brittleness of the existing thin spray support material are solved, and high bond strength, good tensile and flexural resistance and excellent flame retardant properties are achieved, which is suitable for complex geological conditions of coal mine tunnels.
Patent Information
- Application Number
- CN202411776425.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing thin spray support materials have problems such as low bond strength, high brittleness, and easy shrinkage and cracking, which is difficult to meet the complex and changeable geological conditions of coal mine tunnels.
Provided is a non-interlaced thin spray support material, prepared by mixing components A, component B and component C in a specific mass ratio, and components A and component B are added separately, and the curing time is adjusted by adjusting the component ratio to improve the bonding strength and tensile strength.
It has achieved low reaction heat heating, adjustable curing time, high bonding strength, good tensile strength and flexural strength, high tensile elongation, excellent flame retardant and film forming performance, and is suitable for complex geological conditions in coal mine tunnels.
Smart Images

Figure BDA0005171579650000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coal mine tunnel surface support, in particular to a meshless thin shotcrete support material and a preparation method thereof. Background Art
[0002] With the rapid development of the economy, the demand for energy is increasing, the number of coal mines is increasing year by year, and coal mining is gradually developing from shallow mining to deep mining. The requirements for mine tunnel support materials are also gradually increasing.
[0003] Thin shotcrete support is a form of support that uses special thin shotcrete equipment to spray thin shotcrete materials onto the surface of the surrounding rock, quickly penetrate into the cracks of the surrounding rock, and form a thin film on the surface of the surrounding rock. It is particularly suitable for loose, broken, and poorly hydrated mineral rocks. However, existing thin shotcrete materials still have problems such as low bonding strength, high brittleness (fracture elongation <5%), and easy shrinkage and cracking. Summary of the invention
[0004] In response to one or more technical problems existing in the prior art, the present invention provides a meshless thin sprayed support material and a preparation method thereof. The meshless thin sprayed support material provided by the present invention has a small temperature rise caused by heat released by reaction during the application process, an adjustable curing time, high bonding strength, tensile strength, flexural strength and elongation at break and excellent flame retardant properties.
[0005] In a first aspect, the present invention provides a meshless thin-sprayed support material, wherein the meshless thin-sprayed support material is obtained by mixing component A, component B and component C in a mass ratio of 1 to 3:1:1 to 3;
[0006] The raw materials for preparing component A include, by mass fraction, 45% to 65% of polymerized monomers, 3% to 8% of functional monomers, 0.5% to 3% of plasticizers, 2% to 5% of thickeners, 5% to 15% of toughening agents, 10% to 20% of reinforcing resins, 0.5% to 2% of stabilizers, and 1% to 5% of reducing agents;
[0007] The raw materials for preparing component B include, by mass fraction, 30% to 50% of polymerized monomer, 30% to 50% of ABS, 3% to 8% of functional monomer, 1% to 3% of plasticizer, 1% to 3% of thickener, 5% to 10% of toughening agent, 1% to 3% of stabilizer and 1% to 3% of initiator;
[0008] The raw materials for preparing component C include, by mass fraction, 10% to 30% of coupling agent, 40% to 60% of isocyanate, 20% to 30% of polyol, 1% to 5% of active diluent, 1% to 5% of nano silicon dioxide particles, 1% to 3% of defoaming agent, 1% to 5% of catalyst, 1% to 3% of auxiliary agent and 0.1% to 1% of polyaspartic acid ester.
[0009] Preferably, the raw materials for preparing component A include, by mass fraction, 60% to 65% of polymerized monomers, 3% to 5% of functional monomers, 0.5% to 1.5% of plasticizers, 2.5% to 3.5% of thickeners, 8% to 12% of toughening agents, 12% to 15% of reinforcing resins, 0.5% to 1% of stabilizers and 2% to 4% of reducing agents.
[0010] Preferably, the raw materials for preparing component B include, by mass fraction, 35% to 45% of polymerizable monomers, 35% to 45% of ABS, 3% to 5% of functional monomers, 1% to 2% of plasticizers, 1% to 2% of thickeners, 7% to 9% of toughening agents, 1% to 1.5% of stabilizers and 2.5% to 3% of initiators.
[0011] Preferably, the raw materials for preparing component C include, by mass fraction, 15% to 25% coupling agent, 45% to 50% isocyanate, 25% to 30% polyol, 1% to 2% reactive diluent, 2% to 4% nano-silica particles, 1% to 1.5% defoamer, 2% to 4% catalyst, 1% to 1.5% additive and 0.5% to 0.8% polyaspartic acid ester.
[0012] Preferably, the polymerizable monomer is at least one of methacrylic acid, methyl methacrylate, and cyclohexyl methacrylate;
[0013] The functional monomer is a triacrylate, preferably at least one of trimethylolpropane triacrylate and pentaerythritol triacrylate;
[0014] The plasticizer is chlorinated paraffin;
[0015] The thickener is an inorganic salt thickener, preferably silicon dioxide;
[0016] The toughening agent is chloroprene rubber;
[0017] The reinforcing resin is a thermoplastic resin, preferably polymethyl methacrylate;
[0018] Preferably, the stabilizer is an organic stabilizer, preferably p-methoxyphenol;
[0019] The reducing agent is triethylamine; and / or
[0020] The initiator is a peroxide initiator, preferably tert-butyl hydroperoxide.
[0021] Preferably, the coupling agent is a silane coupling agent, preferably at least one of vinyltriethoxysilane and vinyltrimethoxysilane;
[0022] The polyol is a polyester polyol, preferably a polycaprolactone polyol;
[0023] The active diluent is a free radical type active diluent, preferably 1,6-hexanediol diacrylate;
[0024] The catalyst is at least one of dibutyltin dilaurate, stannous octoate, and trimesaldehyde;
[0025] The defoamer is a polyether defoamer, preferably polypropylene glycol; and / or
[0026] The auxiliary agent is a water-based coating auxiliary agent, preferably succinic acid dihydrazide.
[0027] In a second aspect, the present invention provides a method for preparing the mesh-free thin-sprayed support material according to the first aspect, the preparation method comprising:
[0028] Preparation of component A: mixing the polymerizable monomer, the functional monomer, the plasticizer, the thickener, the toughening agent, the reinforcing resin, the stabilizer and the reducing agent to obtain component A;
[0029] Preparation of component B: mixing the polymerizable monomer, the functional monomer, ABS, the plasticizer, the thickener, the toughening agent, the stabilizer and the initiator to obtain component B;
[0030] Preparation of component C: mixing polyol, catalyst, isocyanate, additive, defoamer, coupling agent, nano-silica particles, active diluent and polyaspartic acid ester to obtain component C;
[0031] Component A, component B and component C are mixed evenly to obtain mesh-free thin-spray support material; wherein component A and component B are added separately.
[0032] Preferably, the preparation of component A includes: mixing the polymerizable monomer and the functional monomer, and raising the temperature to 40-45°C, then adding a plasticizer, a thickener, a toughening agent, a reinforcing resin, a stabilizer and a reducing agent and mixing, then raising the temperature of the mixed system to 50-55°C and keeping it warm for 3-5 hours, and finally cooling it to room temperature.
[0033] Preferably, the preparation of component B includes: mixing the polymerizable monomer, the functional monomer and the ABS, and raising the temperature to 40-45°C, then adding the plasticizer, the thickener, the toughening agent, the stabilizer and the initiator and mixing, then raising the temperature of the mixed system to 50-55°C and keeping it warm for 3-5 hours, and finally cooling it to room temperature.
[0034] Preferably, the preparation of component C includes: mixing the polyol, catalyst, isocyanate, additive and defoamer, then raising the temperature to 55-65°C, adding coupling agent, nano-silica particles, active diluent and polyaspartic acid ester and mixing, then raising the temperature of the mixed system to 75-85°C and keeping it warm for 2-4 hours, and finally cooling it to room temperature.
[0035] Compared with the prior art, the present invention has at least the following beneficial effects:
[0036] The mesh-free thin-spray support material provided by the present invention has a small temperature rise caused by the heat released by the reaction during the application process, and the curing time is adjustable. It has high bonding strength, tensile strength, flexural strength and elongation at break, as well as excellent flame retardant properties and film-forming properties, and can meet the use requirements of support materials in the complex and changeable geological conditions of mine tunnels.
[0037] The mesh-free thin-spray support material provided by the present invention can adjust the setting time (curing time) by adjusting the A component, the B component and the C component, and has a wider adjustment range, which can meet the use requirements of the complex and changeable geological conditions of the mine tunnel. During the application process, the temperature rise caused by the heat released by the reaction is small, the expansion multiple is low, and no dust is generated, which is environmentally friendly and non-toxic, and is suitable for mass production. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] In a first aspect, the present invention provides a meshless thin-sprayed support material, wherein the meshless thin-sprayed support material is obtained by mixing component A, component B and component C in a mass ratio of 1 to 3:1:1 to 3;
[0040] The raw materials for preparing component A include, by mass fraction, 45% to 65% of polymerized monomers, 3% to 8% of functional monomers, 0.5% to 3% of plasticizers, 2% to 5% of thickeners, 5% to 15% of toughening agents, 10% to 20% of reinforcing resins, 0.5% to 2% of stabilizers, and 1% to 5% of reducing agents;
[0041] The raw materials for preparing component B include, by mass fraction, 30% to 50% of polymerized monomer, 30% to 50% of ABS, 3% to 8% of functional monomer, 1% to 3% of plasticizer, 1% to 3% of thickener, 5% to 10% of toughening agent, 1% to 3% of stabilizer and 1% to 3% of initiator;
[0042] The raw materials for preparing component C include, by mass fraction, 10% to 30% of coupling agent, 40% to 60% of isocyanate, 20% to 30% of polyol, 1% to 5% of active diluent, 1% to 5% of nano silicon dioxide particles, 1% to 3% of defoaming agent, 1% to 5% of catalyst, 1% to 3% of auxiliary agent and 0.1% to 1% of polyaspartic acid ester.
[0043] The mesh-free thin-spray support material provided by the present invention has a small temperature rise caused by the heat released by the reaction during the application process, and the curing time is adjustable. It has high bonding strength (greater than 5MPa), tensile strength (not less than 0.9MPa), flexural strength (bending angle is not less than 120°) and elongation at break (elongation at break is greater than 37%), as well as excellent flame retardant properties (no burning phenomenon after ignition with an alcohol lamp for 1 minute) and film-forming properties (the surface is smooth and beautiful after film formation), and can meet the use requirements of support materials in the complex and changeable geological conditions of mine tunnels.
[0044] The mesh-free thin-spray support material provided by the present invention can adjust the setting time (curing time) by adjusting the A component, the B component and the C component, and has a wider adjustment range, which can meet the use requirements of the complex and changeable geological conditions of the mine tunnel. During the application process, the temperature rise caused by the heat released by the reaction is small (less than 50°C), the expansion multiple is low, and no dust is generated, which is environmentally friendly and non-toxic, and suitable for mass production.
[0045] According to some preferred embodiments, the raw materials for preparing component A include, by mass fraction, 60% to 65% of polymerized monomers, 3% to 5% of functional monomers, 0.5% to 1.5% of plasticizers, 2.5% to 3.5% of thickeners, 8% to 12% of toughening agents, 12% to 15% of reinforcing resins, 0.5% to 1% of stabilizers, and 2% to 4% of reducing agents.
[0046] According to some preferred embodiments, the raw materials for preparing component B include, by mass fraction, 35% to 45% of polymerized monomers, 35% to 45% of ABS, 3% to 5% of functional monomers, 1% to 2% of plasticizers, 1% to 2% of thickeners, 7% to 9% of toughening agents, 1% to 1.5% of stabilizers and 2.5% to 3% of initiators.
[0047] According to some preferred embodiments, the raw materials for preparing component C include, by mass fraction, 15% to 25% coupling agent, 45% to 50% isocyanate, 25% to 30% polyol, 1% to 2% active diluent, 2% to 4% nano-silica particles, 1% to 1.5% defoamer, 2% to 4% catalyst, 1% to 1.5% additive and 0.5% to 0.8% polyaspartic acid ester.
[0048] According to some preferred embodiments, the polymerizable monomer is at least one of methacrylic acid, methyl methacrylate, and cyclohexyl methacrylate.
[0049] According to some preferred embodiments, the functional monomer is a triacrylate, preferably at least one of trimethylolpropane triacrylate and pentaerythritol triacrylate;
[0050] According to some preferred embodiments, the plasticizer is chlorinated paraffin.
[0051] According to some preferred embodiments, the thickener is an inorganic salt thickener, preferably silicon dioxide.
[0052] According to some preferred embodiments, the toughening agent is chloroprene rubber.
[0053] According to some preferred embodiments, the reinforcing resin is a thermoplastic resin, preferably polymethyl methacrylate.
[0054] According to some preferred embodiments, the stabilizer is an organic stabilizer, preferably p-methoxyphenol.
[0055] According to some preferred embodiments, the reducing agent is triethylamine.
[0056] According to some preferred embodiments, the initiator is a peroxide initiator, preferably tert-butyl hydroperoxide.
[0057] According to some preferred embodiments, the coupling agent is a silane coupling agent, preferably at least one of vinyltriethoxysilane and vinyltrimethoxysilane.
[0058] According to some preferred embodiments, the polyol is a polyester polyol, preferably a polycaprolactone polyol.
[0059] According to some preferred embodiments, the reactive diluent is a free radical reactive diluent, preferably 1,6-hexanediol diacrylate.
[0060] According to some preferred embodiments, the catalyst is at least one of dibutyltin dilaurate, stannous octoate, and trimesaldehyde.
[0061] According to some preferred embodiments, the defoaming agent is a polyether defoaming agent, preferably polypropylene glycol.
[0062] According to some preferred embodiments, the auxiliary agent is a water-based coating auxiliary agent, preferably succinic acid dihydrazide.
[0063] In a second aspect, the present invention provides a method for preparing the mesh-free thin-sprayed support material according to the first aspect, the preparation method comprising:
[0064] Preparation of component A: mixing the polymerizable monomer, the functional monomer, the plasticizer, the thickener, the toughening agent, the reinforcing resin, the stabilizer and the reducing agent to obtain component A;
[0065] Preparation of component B: mixing the polymerizable monomer, the functional monomer, ABS, the plasticizer, the thickener, the toughening agent, the stabilizer and the initiator to obtain component B;
[0066] Preparation of component C: mixing polyol, catalyst, isocyanate, additive, defoamer, coupling agent, nano-silica particles, active diluent and polyaspartic acid ester to obtain component C;
[0067] Component A, component B and component C are mixed evenly to obtain mesh-free thin-spray support material; wherein component A and component B are added separately.
[0068] In some specific embodiments of the present invention, component A and component B are added separately as follows:
[0069] Mix component A and component C, then mix with component B; or
[0070] Mix components B and C, then mix with component A.
[0071] According to some preferred embodiments, the preparation of component A includes: mixing the polymerizable monomer and the functional monomer, and raising the temperature to 40-45°C, then adding a plasticizer, a thickener, a toughening agent, a reinforcing resin, a stabilizer and a reducing agent, and then raising the temperature of the mixed system to 50-55°C and keeping it warm for 3-5 hours, and finally cooling it to room temperature.
[0072] According to some preferred embodiments, the preparation of component B includes: mixing the polymerizable monomer, the functional monomer and the ABS, and raising the temperature to 40-45°C, then adding a plasticizer, a thickener, a toughening agent, a stabilizer and an initiator and mixing, then raising the temperature of the mixed system to 50-55°C and keeping it warm for 3-5 hours, and finally cooling it to room temperature.
[0073] According to some preferred embodiments, the preparation of component C includes: mixing the polyol, catalyst, isocyanate, additive and defoamer, then raising the temperature to 55-65°C, adding a coupling agent, nano-silica particles, an active diluent and polyaspartic acid ester and mixing, then raising the temperature of the mixed system to 75-85°C and keeping it warm for 2-4 hours, and finally cooling it to room temperature.
[0074] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.
[0075] Example 1
[0076] A preparation method of a non-grid thin-spray support material and a preparation method thereof, comprising the following steps:
[0077] Preparation of component A: Weigh 6.5 g of methacrylic acid and 0.4 g of trimethylolpropane triacrylate into a reactor, stir evenly and heat to 40°C, then add 0.1 g of chlorinated paraffin, 0.32 g of silica, 1 g of chloroprene rubber, 1.3 g of polymethyl methacrylate, 0.08 g of p-methoxyphenol, and 0.3 g of triethylamine in sequence, stir evenly and heat to 50°C, continue stirring for 4 hours, cool to room temperature, and obtain component A.
[0078] Preparation of component B: Weigh 4.1 g of methacrylic acid, 4 g of ABS, and 0.4 g of trimethylolpropane triacrylate, put them into a reactor, stir evenly, and heat to 40°C, then add 0.15 g of chlorinated paraffin, 0.15 g of silica, 0.8 g of chloroprene rubber, 0.12 g of p-methoxyphenol, and 0.28 g of tert-butyl hydroperoxide in sequence, stir evenly, and heat to 50°C, continue stirring for 4 hours, and cool to room temperature to obtain component B.
[0079] Preparation of component C: Weigh 2.6 g of polycaprolactone polyol, 0.15 g of dibutyltin dilaurate, and 0.15 g of stannous octoate into a reactor and stir evenly. Then add 4.6 g of isocyanate, 0.1 g of succinic acid dihydrazide, and 0.1 g of polypropylene glycol in sequence, stir evenly, raise the temperature to 60°C, and continue stirring for 2 hours. Then, 1.8 g of vinyl triethoxysilane, 0.3 g of nano-silica particles, 0.14 g of 1,6-hexanediol diacrylate, and 0.06 g of polyaspartic acid ester are added to the reactor in sequence, stir evenly, raise the temperature to 80°C, and continue stirring for 2 hours. Cool to room temperature to obtain component C.
[0080] After mixing component A and component B, mix them evenly with component C. The mass ratio of component A, component B and component C is 1:1:1, and the meshless thin spraying support material is obtained.
[0081] Example 2
[0082] A preparation method of a non-grid thin-spray support material and a preparation method thereof, comprising the following steps:
[0083] Preparation of component A: Weigh 9.75 g of methyl methacrylate and 0.6 g of trimethylolpropane triacrylate into a reactor, stir evenly and heat to 40°C, then add 0.15 g of chlorinated paraffin, 0.48 g of silica, 1.5 g of chloroprene rubber, 1.95 g of polymethyl methacrylate, 0.12 g of p-methoxyphenol, and 0.45 g of triethylamine in sequence, stir evenly and heat to 50°C, continue stirring for 4 hours, cool to room temperature, and obtain component A.
[0084] Preparation of component B: Weigh 2.05 g of methyl methacrylate, 2 g of ABS, and 0.2 g of trimethylolpropane triacrylate into a reactor, stir evenly, and heat to 40°C. Then add 0.075 g of chlorinated paraffin, 0.075 g of silica, 0.4 g of chloroprene rubber, 0.06 g of p-methoxyphenol, and 0.14 g of tert-butyl hydroperoxide in sequence, stir evenly, and heat to 50°C. Continue stirring for 4 hours, cool to room temperature, and obtain component B.
[0085] Preparation of component C: Weigh 3.9 g of polycaprolactone polyol, 0.225 g of stannous octoate, and 0.225 g of trimesaldehyde into a reactor and stir evenly. Then add 6.9 g of isocyanate, 0.15 g of succinic acid dihydrazide, and 0.15 g of polypropylene glycol in sequence, stir evenly, raise the temperature to 60°C, and continue stirring for 2 hours. Then, 2.7 g of vinyltrimethoxysilane, 0.45 g of nano-silica particles, 0.21 g of 1,6-hexanediol diacrylate, and 0.09 g of polyaspartic acid ester are added to the reactor in sequence, stir evenly, raise the temperature to 80°C, and continue stirring for 2 hours. Cool to room temperature to obtain component C.
[0086] Mix component A and component C, and then mix them with component B, wherein the mass ratio of component A, component B and component C is 3:1:3, to obtain a meshless thin-spray support material.
[0087] Example 3
[0088] A preparation method of a non-grid thin-spray support material and a preparation method thereof, comprising the following steps:
[0089] Preparation of component A: Weigh 9.1 g of cyclohexyl methacrylate and 0.56 g of trimethylolpropane triacrylate into a reactor, stir evenly and heat to 40°C, then add 0.14 g of chlorinated paraffin, 0.448 g of silica, 1.4 g of chloroprene rubber, 1.82 g of polymethyl methacrylate, 0.112 g of p-methoxyphenol, and 0.42 g of triethylamine in sequence, stir evenly and heat to 50°C, continue stirring for 4 hours, cool to room temperature, and obtain component A.
[0090] Preparation of component B: Weigh 2.87 g of cyclohexyl methacrylate, 2.8 g of ABS, and 0.28 g of trimethylolpropane triacrylate, put them into a reactor, stir evenly, and heat to 40°C, then add 0.105 g of chlorinated paraffin, 0.105 g of silica, 0.56 g of chloroprene rubber, 0.084 g of p-methoxyphenol, and 0.196 g of tert-butyl hydroperoxide in sequence, stir evenly, and heat to 50°C, continue stirring for 4 hours, and cool to room temperature to obtain component B.
[0091] Preparation of component C: Weigh 3.64 g of polycaprolactone polyol, 0.21 g of dibutyltin dilaurate, and 0.21 g of trimesaldehyde into a reactor and stir evenly. Then add 6.44 g of isocyanate, 0.14 g of succinic acid dihydrazide, and 0.14 g of polypropylene glycol in sequence, stir evenly, raise the temperature to 60°C, and continue stirring for 2 hours. Then, 2.52 g of vinyl triethoxysilane, 0.42 g of nano-silica particles, 0.196 g of 1,6-hexanediol diacrylate, and 0.084 g of polyaspartic acid ester are added to the reactor in sequence, stir evenly, raise the temperature to 80°C, and continue stirring for 2 hours. Cool to room temperature to obtain component C.
[0092] Mix component A and component C, and then mix them with component B, wherein the mass ratio of component A, component B and component C is 2:1:2, to obtain a meshless thin-spray support material.
[0093] Example 4
[0094] A preparation method of a non-grid thin-spray support material and a preparation method thereof, comprising the following steps:
[0095] Preparation of component A: Weigh 3.25 g of methacrylic acid, 3.25 g of methyl methacrylate, and 0.4 g of pentaerythritol triacrylate into a reaction kettle, stir evenly and heat to 40°C, then add 0.1 g of chlorinated paraffin, 0.32 g of silica, 1 g of chloroprene rubber, 1.3 g of polymethyl methacrylate, 0.08 g of p-methoxyphenol, and 0.3 g of triethylamine in sequence, stir evenly and heat to 50°C, continue stirring for 4 hours, cool to room temperature, and obtain component A.
[0096] Preparation of component B: Weigh 2.05 g of methacrylic acid, 2.05 g of methyl methacrylate, 4 g of ABS, and 0.4 g of pentaerythritol triacrylate into a reactor, stir evenly, and heat to 40°C. Then add 0.15 g of chlorinated paraffin, 0.15 g of silica, 0.8 g of chloroprene rubber, 0.12 g of p-methoxyphenol, and 0.28 g of tert-butyl hydroperoxide in sequence, stir evenly, and heat to 50°C. Continue stirring for 4 hours, cool to room temperature, and obtain component B.
[0097] Preparation of component C: Weigh 2.6 g of polycaprolactone polyol and 0.3 g of dibutyltin dilaurate and put them into a reactor, stir evenly, then add 4.6 g of isocyanate, 0.1 g of succinic acid dihydrazide, and 0.1 g of polypropylene glycol in sequence, stir evenly and heat to 60°C, continue stirring for 2 hours, then add 1.8 g of vinyltrimethoxysilane, 0.3 g of nano-silica particles, 0.14 g of 1,6-hexanediol diacrylate, and 0.06 g of polyaspartic acid ester in sequence into the reactor, stir evenly and heat to 80°C, continue stirring for 2 hours, cool to room temperature, and obtain component C.
[0098] Mix component B and component C evenly, and then mix them evenly with component A, wherein the mass ratio of component A, component B and component C is 1:1:1, to obtain a meshless thin-spray support material.
[0099] Example 5
[0100] A preparation method of a non-grid thin-spray support material and a preparation method thereof, comprising the following steps:
[0101] Preparation of component A: Weigh 4.875 g of methacrylic acid, 4.875 g of cyclohexyl methacrylate, and 0.6 g of pentaerythritol triacrylate into a reaction kettle, stir evenly and heat to 40°C, then add 0.15 g of chlorinated paraffin, 0.48 g of silica, 1.5 g of chloroprene rubber, 1.95 g of polymethyl methacrylate, 0.12 g of p-methoxyphenol, and 0.45 g of triethylamine in sequence, stir evenly and heat to 50°C, continue stirring for 4 hours, cool to room temperature, and obtain component A.
[0102] Preparation of component B: Weigh 1.025 g of methacrylic acid, 1.025 g of cyclohexyl methacrylate, 2 g of ABS, and 0.2 g of pentaerythritol triacrylate into a reactor, stir evenly, and heat to 40°C. Then add 0.075 g of chlorinated paraffin, 0.075 g of silica, 0.4 g of chloroprene rubber, 0.06 g of p-methoxyphenol, and 0.14 g of tert-butyl hydroperoxide in sequence, stir evenly, and heat to 50°C. Continue stirring for 4 hours, cool to room temperature, and obtain component B.
[0103] Preparation of component C: Weigh 3.9 g of polycaprolactone polyol and 0.45 g of stannous octoate and put them into a reactor, stir evenly, then add 6.9 g of isocyanate, 0.15 g of succinic acid dihydrazide, and 0.15 g of polypropylene glycol in sequence, stir evenly and raise the temperature to 60°C, continue stirring for 2 hours, then add 2.7 g of vinyl triethoxysilane, 0.45 g of nano-silica particles, 0.21 g of 1,6-hexanediol diacrylate, and 0.09 g of polyaspartic acid ester in sequence into the reactor, stir evenly and raise the temperature to 80°C, continue stirring for 2 hours, cool to room temperature, and obtain component C.
[0104] Mix component A and component C, and then mix them with component B, wherein the mass ratio of component A, component B and component C is 3:1:3, to obtain meshless thin spraying support material.
[0105] Example 6
[0106] A preparation method of a non-grid thin-spray support material and a preparation method thereof, comprising the following steps:
[0107] Preparation of component A: Weigh 4.55 g of methyl methacrylate, 4.55 g of cyclohexyl methacrylate, and 0.56 g of pentaerythritol triacrylate into a reactor, stir evenly and heat to 40°C, then add 0.14 g of chlorinated paraffin, 0.448 g of silica, 1.4 g of chloroprene rubber, 1.82 g of polymethyl methacrylate, 0.112 g of p-methoxyphenol, and 0.42 g of triethylamine in sequence, stir evenly and heat to 50°C, continue stirring for 4 hours, cool to room temperature, and obtain component A.
[0108] Preparation of component B: Weigh 1.435 g of methyl methacrylate, 1.435 g of cyclohexyl methacrylate, 2.8 g of ABS, and 0.28 g of pentaerythritol triacrylate into a reactor, stir evenly, and heat to 40°C. Then add 0.105 g of chlorinated paraffin, 0.105 g of silica, 0.56 g of chloroprene rubber, 0.084 g of p-methoxyphenol, and 0.196 g of tert-butyl hydroperoxide in sequence, stir evenly, and heat to 50°C. Continue stirring for 4 hours, cool to room temperature, and obtain component B.
[0109] Preparation of component C: Weigh 3.64 g of polycaprolactone polyol and 0.42 g of trimesaldehyde into a reactor and stir evenly. Then add 6.44 g of isocyanate, 0.14 g of succinic acid dihydrazide and 0.14 g of polypropylene glycol in sequence, stir evenly and heat to 60°C, continue stirring for 2 hours, then add 2.52 g of vinyltrimethoxysilane, 0.42 g of nano-silica particles, 0.196 g of 1,6-hexanediol diacrylate and 0.084 g of polyaspartic acid ester in sequence into the reactor, stir evenly and heat to 80°C, continue stirring for 2 hours, cool to room temperature to obtain component C.
[0110] Mix component A and component C, and then mix them with component B, wherein the mass ratio of component A, component B and component C is 2:1:2, to obtain a meshless thin-spray support material.
[0111] Comparative Example 1
[0112] It is basically the same as Example 2, except that the mass ratio of component A, component B and component C is 3:1:6.
[0113] Comparative Example 2
[0114] The method is basically the same as Example 2, except that the content of trimethylolpropane triacrylate in component A is 0.1 g, that is, trimethylolpropane triacrylate accounts for 1% of the raw materials for preparing component A.
[0115] Comparative Example 3
[0116] It is basically the same as Example 2, except that component C is not included.
[0117] Comparative Example 4
[0118] It is basically the same as Example 2, except that the mass ratio of component A, component B and component C is 0.5:1:3.
[0119] Comparative Example 5
[0120] It is basically the same as Example 2, except that the mass ratio of component A, component B and component C is 5:1:3.
[0121] Comparative Example 6
[0122] It is basically the same as Example 2, except that the mass ratio of component A, component B and component C is 3:0.5:3.
[0123] Comparative Example 7
[0124] It is basically the same as Example 2, except that component A, component B and component C are mixed together.
[0125] In order to verify the performance of this non-grid thin shotcrete support material, a series of evaluation experiments were carried out, as follows:
[0126] Tensile strength and elongation at break tests
[0127] The method is as follows: a layer of plastic film is placed at the bottom of a petri dish (7 cm in diameter), and then the product is placed in the petri dish in a liquid state. The sample is placed in a drying oven at 55°C for 5 to 6 hours. The formed film is taken out, and the plastic film at the bottom is removed to obtain a film with a diameter of 7 cm and a thickness of 5 mm. The prepared product is clamped at the upper end, and the upper end is clamped with a mold of a WDS-5 digital display universal testing machine, and then the bottom is fixed, and the moving speed is set to 5 mm / min. The tensile strength of the test product is measured, and the elongation at break is calculated.
[0128] Bond strength test
[0129] The method is as follows: Use a viscometer to measure the viscosity coefficient of the product: Place the samples of each embodiment and comparative example between two 5cm×5cm×5cm concrete slabs, and after drying, use a TFW-10S computer electronic universal testing machine to perform a tensile test, and set the test speed to 10 mm / min.
[0130] Flame retardancy test
[0131] The method is as follows: 10 grams of the sample of each embodiment and comparative example is placed on a 10 cm×20 cm steel plate. After the product is dried, it is burned with an alcohol lamp for 1 minute. After evacuation, the phenomenon is observed and the time is recorded.
[0132] The properties of the sprayed materials prepared in the embodiments and comparative examples of the present invention were measured by the above method, as shown in Table 1.
[0133] Table 1. Performance data of non-grid thin spraying support materials prepared in various embodiments of the present invention and comparative examples
[0134]
[0135] As can be seen from Table 1, the spray material prepared in the embodiment of the present invention can ensure that the temperature rise caused by the heat released by the reaction during the application process is less than 50°C, the expansion multiple is less than 1.2 times, the curing time is adjustable within 3 to 30 minutes, the tensile strength is not less than 0.9 MPa (1d), the elongation at break is greater than 37%, the bonding strength is greater than 5 MPa, the bending angle is not less than 120°, the flame retardant performance is good, and there is still no burning phenomenon after being ignited by an alcohol lamp for 1 minute. The comprehensive performance is significantly better than the spray material prepared in the comparative example.
[0136] In summary, the preparation process of the non-grid thin spray support material provided by the present invention is simple, the comprehensive cost is low, and no dust is generated during the application process, which is environmentally friendly and non-toxic. The non-grid thin spray support material has a small temperature rise caused by the heat released by the reaction during the application process, a low expansion multiple, an adjustable curing time, and has more excellent mechanical properties and flame retardant properties.
[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A mesh-free thin-spray support material, characterized in that: The mesh-free thin shotcrete support material is obtained by mixing component A, component B and component C in a mass ratio of 1 to 3:1:1 to 3; The raw materials for preparing component A include, by mass fraction, 45% to 65% of polymerized monomers, 3% to 8% of functional monomers, 0.5% to 3% of plasticizers, 2% to 5% of thickeners, 5% to 15% of toughening agents, 10% to 20% of reinforcing resins, 0.5% to 2% of stabilizers, and 1% to 5% of reducing agents; The raw materials for preparing component B include, by mass fraction, 30% to 50% of polymerized monomer, 30% to 50% of ABS, 3% to 8% of functional monomer, 1% to 3% of plasticizer, 1% to 3% of thickener, 5% to 10% of toughening agent, 1% to 3% of stabilizer and 1% to 3% of initiator; The raw materials for preparing component C include, by mass fraction, 10% to 30% of coupling agent, 40% to 60% of isocyanate, 20% to 30% of polyol, 1% to 5% of active diluent, 1% to 5% of nano silicon dioxide particles, 1% to 3% of defoaming agent, 1% to 5% of catalyst, 1% to 3% of auxiliary agent and 0.1% to 1% of polyaspartic acid ester.
2. The mesh-free thin-spray support material according to claim 1 is characterized in that: The raw materials for preparing component A include, by mass fraction, 60% to 65% of polymerized monomers, 3% to 5% of functional monomers, 0.5% to 1.5% of plasticizers, 2.5% to 3.5% of thickeners, 8% to 12% of toughening agents, 12% to 15% of reinforcing resins, 0.5% to 1% of stabilizers and 2% to 4% of reducing agents.
3. The mesh-free thin-spray support material according to claim 1 is characterized in that: The raw materials for preparing component B include, by mass fraction, 35% to 45% of polymerized monomers, 35% to 45% of ABS, 3% to 5% of functional monomers, 1% to 2% of plasticizers, 1% to 2% of thickeners, 7% to 9% of toughening agents, 1% to 1.5% of stabilizers and 2.5% to 3% of initiators.
4. The mesh-free thin-spray support material according to claim 1 is characterized in that: The raw materials for preparing component C include, by mass fraction, 15% to 25% of coupling agent, 45% to 50% of isocyanate, 25% to 30% of polyol, 1% to 2% of active diluent, 2% to 4% of nano silicon dioxide particles, 1% to 1.5% of defoaming agent, 2% to 4% of catalyst, 1% to 1.5% of auxiliary agent and 0.5% to 0.8% of polyaspartic acid ester.
5. The mesh-free thin-spray support material according to claim 1 is characterized in that: The polymerizable monomer is at least one of methacrylic acid, methyl methacrylate, and cyclohexyl methacrylate; The functional monomer is a triacrylate, preferably at least one of trimethylolpropane triacrylate and pentaerythritol triacrylate; The plasticizer is chlorinated paraffin; The thickener is an inorganic salt thickener, preferably silicon dioxide; The toughening agent is chloroprene rubber; The reinforcing resin is a thermoplastic resin, preferably polymethyl methacrylate; The stabilizer is an organic stabilizer, preferably p-methoxyphenol; The reducing agent is triethylamine; and / or The initiator is a peroxide initiator, preferably tert-butyl hydroperoxide.
6. The mesh-free thin-spray support material according to claim 1 is characterized in that: The coupling agent is a silane coupling agent, preferably at least one of vinyl triethoxy silane and vinyl trimethoxy silane; The polyol is a polyester polyol, preferably a polycaprolactone polyol; The active diluent is a free radical type active diluent, preferably 1,6-hexanediol diacrylate; The catalyst is at least one of dibutyltin dilaurate, stannous octoate, and trimesaldehyde; The defoamer is a polyether defoamer, preferably polypropylene glycol; and / or The auxiliary agent is a water-based coating auxiliary agent, preferably succinic acid dihydrazide.
7. A method for preparing the meshless thin-sprayed support material according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Preparation of component A: mixing the polymerizable monomer, the functional monomer, the plasticizer, the thickener, the toughening agent, the reinforcing resin, the stabilizer and the reducing agent to obtain component A; Preparation of component B: mixing the polymerizable monomer, the functional monomer, ABS, the plasticizer, the thickener, the toughening agent, the stabilizer and the initiator to obtain component B; Preparation of component C: mixing polyol, catalyst, isocyanate, additive, defoamer, coupling agent, nano-silica particles, active diluent and polyaspartic acid ester to obtain component C; Component A, component B and component C are mixed evenly to obtain mesh-free thin-spray support material; wherein component A and component B are added separately.
8. The preparation method according to claim 7, characterized in that: The preparation of component A includes: mixing the polymerizable monomer and the functional monomer, raising the temperature to 40-45°C, then adding a plasticizer, a thickener, a toughening agent, a reinforcing resin, a stabilizer and a reducing agent, and then raising the temperature of the mixed system to 50-55°C and keeping it warm for 3-5 hours, and finally cooling it to room temperature.
9. The preparation method according to claim 7, characterized in that: The preparation of component B includes: mixing the polymerizable monomer, the functional monomer and the ABS, raising the temperature to 40-45°C, then adding the plasticizer, the thickener, the toughening agent, the stabilizer and the initiator, and then raising the temperature of the mixed system to 50-55°C and keeping it warm for 3-5 hours, and finally cooling it to room temperature.
10. The preparation method according to claim 7, characterized in that: The preparation of component C includes: mixing polyol, catalyst, isocyanate, additive and defoamer, then raising the temperature to 55-65°C, adding coupling agent, nano-silica particles, active diluent and polyaspartic acid ester and mixing, then raising the temperature of the mixed system to 75-85°C and keeping it warm for 2-4 hours, and finally cooling it to room temperature.